2019
DOI: 10.1002/gcc.22739
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular and clinicopathological analysis of vascular malformations: A study of 319 cases

Abstract: Vascular malformations are part of overgrowth syndromes characterized by somatic mosaic mutations or rarely by germline mutations. Due to their similarities and diversity, clinicopathological classification can be challenging. A comprehensive targeted Next Generation Sequencing screen using Unique Molecular Identifiers with a technical sensitivity of 1% mutant alleles was performed for frequently mutated positions in ≥21 genes on 319 formalin‐fixed paraffin‐embedded samples. In 132 out of 319 cases pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 45 publications
0
62
0
Order By: Relevance
“…WT1 immunohistochemistry can be helpful in discriminating vascular neoplasms from malformations with absence of cytoplasmic staining in lymphatic, venous and capillary malformations [42]. Mutationally affected genes include PIK3CA, TEK (TIE2), AKT, GNAQ, GNA11, KRAS, NRAS, PTEN and RASA [43].…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…WT1 immunohistochemistry can be helpful in discriminating vascular neoplasms from malformations with absence of cytoplasmic staining in lymphatic, venous and capillary malformations [42]. Mutationally affected genes include PIK3CA, TEK (TIE2), AKT, GNAQ, GNA11, KRAS, NRAS, PTEN and RASA [43].…”
Section: Vascular Malformationsmentioning
confidence: 99%
“…Periinterventional imaging should verify the clinically suspected diagnosis of a vascular anomaly and provide sufficient information for precise treatment planning [12,13]. The goal of this over-view of the essentials in periinterventional imaging of peripheral vascular anomalies is to simplify the diagnostic approach and the interdisciplinary management of this rare disease.…”
Section: Introductionmentioning
confidence: 99%
“…12 Intriguingly, a recent study revealed that several somatic KRAS mutations like KRAS c.64C>A (p.Gln22Lys) and c.436G>A (p.Ala146Thr) were associated with combined phenotypes of Klippel-Trenaunay syndrome and port-wine stains. 2 In this study, we found a novel KRAS c.182_183delinsTC (p.Q61L) mutation in the patient with Klippel-Trenaunay syndrome.…”
Section: Discussionmentioning
confidence: 59%
“…1 In contrast, Klippel-Trenaunay syndrome is a sporadic congenital vascular malformation with the most common somatic PIK3CA mutations as well as infrequent KRAS mutations, and distinguished by extensive portwine stains involving limbs and/or trunk associated with hypertrophy of soft tissue or bone and venous varicosities. 2,3 To date, Klippel-Trenaunay and Sturge-Weber overlap syndrome has been reported in several studies, where only the most common somatic GNAQ c.548G>A (p.R183Q) mutation without any other known mutations has been found. [4][5][6] Nevertheless, whether a single somatic GNAQ mutation is responsible for the whole phenotypes remains to be determined.…”
Section: Introductionmentioning
confidence: 99%